Development of recombinant subunit vaccines against Flavobacterium covae and Flavobacterium columnare in grass carp (Ctenopharyngodon idellus): Evaluation of protective efficacy and antibody immune response - Zhongning He; Rui Han; Huicheng Wu; Xueming Dan; Yanwei Li; Zequan Mo (Aquaculture, 2027)

Methylotrophic rewiring enhances methane recovery and stability in semi-thermophilic anaerobic digestion of protein-rich food waste - Changxun Zhao; Jiefei Mo; Xingkun Xu; Yabin Gong; Yun Chen; Ouru Zhan; Huan Zheng; Dan Lu; Yong Qin; Weixiang Wu (Water Research, 2026)

Harnessing the pyrophosphate-triggered disassembly of MIL-88B(Fe) for in situ dual-signal generation and reliable acetamiprid detection - Bo Zhao; Xiuxian Mo; Jiayao Wang; Akang Dan; Tong Chen; Dan Ouyang; Xiaopeng Hu (Food Chemistry, 2026)

Lunar water cycle and D/H fractionation driven by solar wind implantation and micrometeorite impacts - Chuanjiao Zhou; Hong Tang; Xiongyao Li; Bing Mo; Wen Yu; Dan Zhu; Yuanyun Wen; Jianzhong Liu (Earth and Planetary Science Letters, 2026)

Development of an innovative in-situ solid-state fermentation system based on endophytic fungi and agrifood by-products pigeon pea roots to enhance genistein production - Jin-Xian Fu; Mo-Nan Wen; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Dan Qu (Innovative Food Science & Emerging Technologies, 2026)

Lactiplantibacillus plantarum SP055 pretreatment attenuates experimental colitis in association with partial preservation of epithelial integrity and microbial-metabolic homeostasis - Jianwei Zang; Xiaotong Hao; Yibo Shi; Xia Fan; Yimeng Kou; Xiaogan Zhao; Qiaoya Mo; Di Yu; Jiamin Xu; Chunling Meng; Chang Xu; Luyao Xiao; et al. (Food Bioscience, 2026)

Long-term protective efficacy and distinct immune responses of live and inactivated vaccines against cryptocaryoniasis in orange-spotted grouper (Epinephelus coioides) - Hai Zhang; Huicheng Wu; Shunli Che; Yuhao Hong; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Mechanistic study of the anti-photoaging effects of Mogroside V via the VEGFA/PI3K-Akt signaling pathway in human fibroblasts - Qiuting Mo; Keran Jia; Xiaoyu Wang; Changtao Wang; Dongdong Wang; Dan Zhao; Jiachan Zhang; Meng Li (Food Bioscience, 2026)

CO2-responsive ethyl cellulose–microsphere films for postharvest freshness monitoring of fresh products - Daoyu Liu; Liangbin Hu; Enbo Xu; Huan Cheng; Hongbo Li; Dan Xu; Jiayi Zhang; Lishan Yao; Lu Tian; Xiaolin Zhu; Feilei Zhu; Jing Wang; et al. (Food Control, 2026)

Zein-based films with γ-cyclodextrin metal organic framework/oregano essential oil for fruit preservation - Zhenbin Liu; Fengbing Yang; Liangbin Hu; Dan Xu; Guoqiang Zhang; Yumei Liao; Min Cui; Hongbo Li; Haizhen Mo (Food Packaging and Shelf Life, 2026)

Recombinant fusion subunit vaccine provides enhanced immune protection against Cryptocaryon irritans infection in grouper - Huicheng Wu; Zhengli Wei; Li Yang; Yihao Cen; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Atomic condensation of Na and K vapor followed by oxidation in lunar impact glass beads revealed by Chang’E-6 - Ming-Yang Li; Ying-Kui Xu; Dan Zhu; De-Liang Wang; Yi-Cao Zhou; Bing Mo; Shi-Jie Li; Yang Li; Xiong-Yao Li; Jian-Zhong Liu; Wei Du; Yun Liu (Earth and Planetary Science Letters, 2026)

Shrubs rather than microbial fertilizer promoted the establishment of dominant trees in a subalpine forest - Ruijuan Zhong; Dan Mo; Yinzhan Liu; Shuang Xiang; Shucun Sun (Forest Ecology and Management, 2026)

Dynamic assessment of NO2 plume rise and pollution contributions from steel industry point sources in an energy-intensive region of China - Chao Gao; Xuelei Zhang; Mo Dan; Ling Huang; Hongmei Zhao; Shichun Zhang; Aijun Xiu (Atmospheric Pollution Research, 2026)

Systematic Identification, Characterization, and Expression Analysis of Genes Encoding C2H2-Type Zinc Finger Proteins in Rice Associated with Anilofos and Bentazone Metabolism - Ying Yu Zeng; Zhi Zhong Zhou; Yang Yang Mo; Li Qing Zeng; Xiao Lu Wang; Zhi Jiang He; Lan Xin Huang; Dan Lu; Zhao Jie Chen (Tropical Plant Biology, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Exploring mussel adhesive protein as a natural Pickering emulsion stabilizer for 3D food printing applications - Zinuo An; Liangbin Hu; Xiaoyue Gong; Wenjing Wang; Jianli Zhang; Haizhen Mo; Dan Xu; Zhenbin Liu (Journal of Food Engineering, 2026)

Co-infection of Cryptocaryon irritans and Vibrio harveyi impairs osmoregulatory and respiratory functions in orange-spotted grouper Epinephelus coioides - Xueli Lai; Haoran Tang; Huicheng Wu; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

First report of marine leech Limnotrachelobdella okae infestation in miiuy croaker (Miichthys miiuy): An emerging threat to Chinese mariculture - Shunli Che; Zequan Mo; Hai Zhang; Haoran Tang; Xueming Dan; Yanwei Li (Veterinary Parasitology, 2026)

Lopinavir/ritonavir induces hepatotoxicity in HepG2 cells through inhibition of the Nrf2 pathway, resulting in oxidative stress, endoplasmic reticulum stress, and cell cycle arrest - Wenhong Zhou; Dan Wang; Jundou Tu; Jun Li; Jiayu Xu; Wenjing Tan; Diwei Mo; Pengying Liang; Yinglin Guo; Ming Hu; Linhu Ye (Toxicology Letters, 2026)

Photothermal-activated self-healing MXene hydrogel for diabetic wound healing with polyphenol synergy - Siqi Ye; Dan He; Tao Chen; Keng-Fu Lan; Yongjin Zhong; Yancheng Lai; Yingying Wu; Anchun Mo (Chemical Engineering Journal, 2026)

A dual-functional CdS QDs/Ag@AgTaO3 heterojunction for continuous remediation of nitroaromatic contaminated water - Fang Wang; Mingzu Cao; Yueyang Chen; Xuelei Li; Dan He; Baichuan Mo (Journal of Environmental Chemical Engineering, 2025)

Multivalent copper-carbon-catalyzed persulfate/O2 system: The relation between copper valence and the species of reactive oxygen - Zehui Fan; Zhisen Li; Dan Mo; Jingyang Zhang; Shuyi Yang; Yun Li; Changlong Bi; Chong Peng; Tao E (Journal of Environmental Chemical Engineering, 2025)

Prion-inhibition-like protein (PiP) governs Aspergillus flavus spore dormancy under postharvest drying stress: A novel target for aflatoxin mitigation in grain storage systems - Chen Xuan; Feng Chengyuan; Liu Mengdan; Meng Ruitong; Xu Dan; Yao Lishan; Li Hongbo; Mo Haizhen; Hu Liangbin; Zhou Xiaohui (Food Microbiology, 2025)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Characterisation and diagnostic model of monogenic lupus - Mengyang Yang; Dan Lu; Yulu Li; Xiongbin Chen; Han Yang; Wenxiu Mo; Huawei Mao (Immunologic Research, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

Groundwater quality and risk assessment in urban areas of arid regions on the western Qinghai-Tibet Plateau - Qingshan Li; Xiaobing Kang; Mo Xu; Dan Wang; Ke Li (Groundwater for Sustainable Development, 2025)

Effect of subcutaneous injection vaccine on protection against Cryptocaryon irritans infection - Huicheng Wu; Yingtong Hu; Yipei Lu; Yanwei Li; Xueming Dan; Zequan Mo (Aquaculture, 2025)

Electrocatalytic oxidation of ranitidine using a fluorinated blue titanium dioxide nanotube array electrode - Jianhui Xu; Zhijie Cui; Xin Fu; Dan Li; Yanyan Zeng; Yunfei Zhang; Peng Liu; Xiangteng Mo; Kexin Cao; Zijie Shen; Shangkun Ye (Journal of Environmental Chemical Engineering, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Polar components in biochar boost oxygen vacancies and electron transfer for enhancing the degradation of tetracycline - Dan Mo; Jingyang Zhang; Jiaqi Zhao; Chong Peng; Yuanfei Wang; Tao E (Journal of Environmental Management, 2025)

Transcranial temporal interference stimulation precisely targets deep brain regions to regulate eye movements - Mo Wang; Sixian Song; Dan Li; Guangchao Zhao; Yu Luo; Yi Tian; Jiajia Zhang; Quanying Liu; Pengfei Wei (Neuroscience Bulletin, 2025)
Transcranial temporal interference stimulation (tTIS) is a novel non-invasive neuromodulation technique with the potential to precisely target deep brain structures. This study explores the neural and behavioral effects of tTIS on the superior colliculus (SC), a region involved in eye movement control, in mice. Computational modeling revealed that tTIS delivers more focused stimulation to the SC than traditional transcranial alternating current stimulation. In vivo experiments, including Ca 2+ signal recordings and eye movement tracking, showed that tTIS effectively modulates SC neural activity and induces eye movements. A significant correlation was found between stimulation frequency and saccade frequency, suggesting direct tTIS-induced modulation of SC activity. These results demonstrate the precision of tTIS in targeting deep brain regions and regulating eye movements, highlighting its potential for neuroscientific research and therapeutic applications.

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Hyperspectral inversion of rare earth element concentration based on SPA-PLSR model - Dan Ke; Wenkai Wang; Huan Mo; Fawang Ye; Wei Chen; Wanming Zhang; Sirui Wang (Ore and Energy Resource Geology, 2025)

Impacts of live and artificial feed on histology, biochemical indicators, gene expression, and bacterial resistance in mandarin fish (Siniperca chuatsi) - Shunli Che; Jiawei Chen; Hai Zhang; Weizhen Xu; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2025)

Improving both energetic and kinetic performances of osmotic battery for grid energy storage - Dan Li; Zijing Mo; Anthony G. Fane; Qianhong She (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

The influence of different flavor peptides on brain perception via scalp electroencephalogram and development of a taste model - Hongbo Li; Xuchao Feng; Zhenbin Liu; Wenting Wang; Lufei Tian; Dan Xu; Bimal Chitrakar; Zhenkun Cui; Liangbin Hu; Haizhen Mo (Food Chemistry, 2025)

XR-based interactive visualization platform for real-time exploring dynamic earth science data - Xuelei Zhang; Hu Yang; Chunhua Liu; Qingqing Tong; Aijun Xiu; Lingsheng Kong; Mo Dan; Chao Gao; Meng Gao; Huizheng Che; Xin Wang; Guangjian Wu (Environmental Modelling & Software, 2025)

Cascade energy transfer endows phosphorescent carbon dots-based films with tunable and broadband afterglow for fingerprint recognition and anticounterfeiting - Zhanpeng Liu; Xiangbo Ding; Lin Cai; Yihan Jia; Xia Ran; Zhongzheng Guo; Dan Mo; Yatao Pan; Lijun Guo (Chemical Engineering Journal, 2025)

Construction of multi-pathway electron transfer channel: Mechanism on non-radical to radical promotion in electrocatalysis - Jingyang Zhang; Zhisen Li; Zehui Fan; Dan Mo; Shuyi Yang; Yun Li; E Tao (Chemical Engineering Journal, 2025)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

The predominant role of IgM in grouper (Epinephelus coioides) mucosal defense against ectoparasitic protozoan infection - Zequan Mo; Huajian Lin; Xueli Lai; Pengbo Dan; Huicheng Wu; Xiaochun Luo; Xueming Dan; Yanwei Li (Fish & Shellfish Immunology, 2024)

Ferrous sulfate remodels the properties of sodium alginate-based hydrogel and facilitates the healing of wound infection caused by MRSA - Zhen Wang; Zinuo An; Aurore Richel; Minmin Huang; Xingchun Gou; Dan Xu; Min Zhang; Haizhen Mo; Liangbin Hu; Xiaohui Zhou (Carbohydrate Polymers, 2024)

Lactococcus garvieae as a Novel Pathogen in Cultured Pufferfish (Takifugu obscurus) in China - Ruilong Xu; Zhongning He; Yiyang Deng; Yihao Cen; Zequan Mo; Xueming Dan; Yanwei Li (Fishes, 2024)
In October 2023, a disease outbreak in pufferfish (Takifugu obscurus) farms in Zhongshan City, Guangdong, China, caused high mortality. Diseased fish (mean length: 15 ± 1 cm) exhibited swimming disorders, fin rot, hemorrhage, and an enlarged spleen. Histopathological observations generally revealed inflammation, necrosis, and congestion in the spleen, kidneys, and brain tissues. The most severe pathological changes included interstitial edema and tubular atrophy in the kidneys, hemosiderin deposition in the spleen, massive red blood cell infiltration, and a decrease in lymphocytes. A single strain of bacteria (Tol-1) was isolated from the diseased pufferfish and identified as a Gram-positive streptococcus strain, exhibiting α-hemolysis on sheep blood agar plates. Through biochemical characterization, 16S rDNA sequencing, morphological analysis, and specific primer-based identification, the Tol-1 strain was identified as Lactococcus garvieae, serotype I. Antimicrobial susceptibility testing indicated that Tol-1 was sensitive to Chloramphenicol, Ampicillin, Cephalexin, and Doxycycline, but resistant to Kanamycin, Gentamicin and Ciprofloxacin. In addition, 15 common virulence factors were detected in the Tol-1 strain, including adhPav, adhPsaA, adhC I–II, adh, and hly 1–3. Pufferfish (mean length: 17 ± 1 cm) subjected to artificial infection via intraperitoneal injection (IP) with the Tol-1 strain exhibited clinical symptoms and histopathological damage similar to those observed in naturally infected fish. An infection dose of 1 × 105 CFU/fish resulted in 80% mortality. The study fulfilled Koch’s postulates, indicating that the disease outbreak in pufferfish was caused by L. garvieae, which exhibited a high mortality rate in pufferfish despite the subtle clinical symptoms. These results serve as a warning for pufferfish farming areas and provide a scientific basis for future prevention and control efforts.

Identification of flavor peptides based on virtual screening and molecular docking from Hypsizygus marmoreuss - Wenting Wang; Hongbo Li; Zhenbin Liu; Dan Xu; Huayin Pu; Liangbin Hu; Haizhen Mo (Food Chemistry, 2024)

Organic coating strategy with oxidized oxygen anion capture to suppress lattice oxygen evolution of Ni-rich cathode materials at high voltage - Yizhen Huang; Manling Tao; Li Mo; Lu Zheng; Dan Su; Juantao Jiang; Qichang Pan; Sijiang Hu; Hongqiang Wang; Qingyu Li; Fenghua Zheng (Chemical Engineering Journal, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

A multifunctional desalination-osmotic energy storage (DOES) system for managing energy and water supply - Dan Li; Zijing Mo; Anthony G. Fane; Qianhong She (Desalination, 2024)

Germination and growth of corn submitted to sowing and cultivation management by subsurface drip irrigation in the North China Plain - Yan Mo; Yanqun Zhang; Dan Wang; Jiandong Wang; Guangyong Li; Shihong Gong; Xiaoyan Gao (Irrigation Science, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Pickering emulsion gel stabilized by Auricularia auricula protein - Yunxia Liang; Zhenbin Liu; Huan Liu; Dan Xu; Liangbin Hu; Bimal Chitrakar; Haizhen Mo; Li Hongbo (Journal of Food Engineering, 2024)

Preparation of Pleurotus eryngii protein baked food by 3D printing - Shuang Lv; Hongbo Li; Zhenbin Liu; Shangqiao Cao; Lishan Yao; Zhenbao Zhu; Liangbin Hu; Dan Xu; Haizhen Mo (Journal of Food Engineering, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Corrigendum to “Over-expression of miR-100 is responsible for the low-expression of ATM in the human glioma cell line: M059J” [DNA Repair 9 (2010) 1170-1175] - Wooi Loon Ng; Dan Yan; Xiangming Zhang; Yin-Yuan Mo; Ya Wang (DNA Repair, 2024)

3D printing of curcumin enriched Pickering emulsion gel stablized by pea protein-carrageenan complexes - Zhenbin Liu; Siyu Ha; Chaofan Guo; Dan Xu; Liangbin Hu; Hongbo Li; Subrota Hati; Haizhen Mo (Food Hydrocolloids, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Streptomyces cynarae sp. nov., a novel actinomycete isolated from the leaves of Cynara scolymus L - Aihua Deng; Yijia Luo; Can Wu; Dan Chen; Ping Mo; Baiyuan Li (Antonie van Leeuwenhoek, 2023)

Manganese improved Trachinotus ovatus immune against Cryptocaryon irritans infection - Huicheng Wu; Xueli Lai; Wenjie Guo; Xiong Li; Yingtong Hu; Xueming Dan; Yanwei Li; Zequan Mo (Aquaculture, 2023)

Walnut protein-based 3D printed cream substitute - Hongbo Li; Wenting Wang; Na Li; Zhenbin Liu; Dan Xu; Huayin Pu; Weize Liang; Haizhen Mo; Liangbin Hu (Journal of Food Engineering, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Immobilization antigens provide orange-spotted grouper (Epinephelus coioides) protection against Cryptocaryon irritans infection - Xiong Li; Hongping Chen; Yihao Cen; Jiule Wang; Na Ni; Xueming Dan; Zequan Mo; Yanwei Li (Aquaculture, 2023)

Hydrophobic modified PET ion track-etched membrane for oil/water separation - Zaichao Guo; Yujing Wang; Zhihao Liang; Zhenhua Zhang; Jianjun Xie; Xiaoyu Gui; Borui Hou; Dan Mo; Liang Lu; Huijun Yao (Journal of Water Process Engineering, 2023)

A “smart-sensing” bactericidal protein-based Pickering emulsion - Lishan Yao; Rui Wang; Shurui Peng; Zhenbin Liu; Hongbo Li; Dan Xu; Liangbin Hu; Haizhen Mo (Journal of Food Engineering, 2023)

Vibrio harveyi co-infected with Cryptocaryon irritans to orange-spotted groupers Epinephelus coioides - Xueli Lai; Huicheng Wu; Wenjie Guo; Xiong Li; Jiule Wang; Yafei Duan; Peng Zhang; Zelin Huang; Yanwei Li; Guixin Dong; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2023)

Blended cumin/Zanthoxylum essential oil improve the antibacterial, fresh-keeping performance and flavor of chilled fresh mutton - Hongbo Li; Lili Zhao; Quanyu Dai; Haizhen Mo; Zhenbin Liu; Huayin Pu; Xiaolin Zhu; Lishan Yao; Dan Xu; Liangbin Hu (Meat Science, 2023)

Proposal of Streptomyces sporoverrucosus Gause et al. 1983 as a later heterotypic synonym of Streptomyces goshikiensis Niida et al. 1966 and an emended description of Streptomyces goshikiensis - Ping Mo; Lu Xu; Dan Chen; Zhongyuan Chen; Baiyuan Li (Antonie van Leeuwenhoek, 2023)

Refined assessment and decomposition analysis of carbon emissions in high-energy intensive industrial sectors in China - Yali Tong; Kun Wang; Jieyu Liu; Yun Zhang; Jiajia Gao; Mo Dan; Tao Yue; Penglai Zuo; Ziying Zhao (Science of The Total Environment, 2023)

Incorporation of probiotics into 3D printed Pickering emulsion gel stabilized by tea protein/xanthan gum - Dan Xu; Zhenbin Liu; Zinuo An; Liangbin Hu; Hongbo Li; Haizhen Mo; Subrota Hati (Food Chemistry, 2023)

Pea protein-xanthan gum interaction driving the development of 3D printed dysphagia diet - Zhenbin Liu; Xi Chen; Quanyu Dai; Dan Xu; Liangbin Hu; Hongbo Li; Subrota Hati; Bimal Chitrakar; Lishan Yao; Haizhen Mo (Food Hydrocolloids, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

3D printed dysphagia diet designed from Hypsizygus marmoreus by-products with various polysaccharides - Zhenbin Liu; Xuebing Xing; Haizhen Mo; Dan Xu; Liangbin Hu; Hongbo Li; Bimal Chitrakar (Journal of Food Engineering, 2023)

Preparation of Pickering emulsion gel stabilized by tea residue protein/xanthan gum particles and its application in 3D printing - Zinuo An; Zhenbin Liu; Haizhen Mo; Liangbin Hu; Hongbo Li; Dan Xu; Bimal Chitrakar (Journal of Food Engineering, 2023)

Application of loofah and insects in a bio-trickling filter to relieve clogging - Yun Zhang; Yali Tong; Kun Wang; Quanming Liang; Jieyu Liu; Xiaoxi Zhang; Xiaohui Ji; Jiajia Gao; Penglai Zuo; Mo Dan (Chemosphere, 2023)

Prediction of seismic acceleration response of precast segmental self-centering concrete filled steel tube single-span bridges based on machine learning method - Dan Zhang; Yuang Chen; Chen Zhang; Guixiang Xue; Junfei Zhang; Mo Zhang; Ling Wang; Ning Li (Engineering Structures, 2023)

Effects of Cryptocaryon irritans infection on the histopathology, oxidative stress, immune response, and intestinal microbiota in the orange-spotted grouper Epinephelus coioides - Shimin Zeng; Yafei Duan; Xiong Li; Yingtong Hu; Zequan Mo; Xueming Dan; Yanwei Li (Fish & Shellfish Immunology, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Selection of Payloads for Antibody–Drug Conjugates Targeting Ubiquitously Expressed Tumor-Associated Antigens: a Case Study - Bing Yao; Xiao Gao; Mo Dan; Can Yuan; Xixin Hu; Zhaopeng Sun; Xiwu Hui; Boning Liu; Pingkai Ouyang; Guoguang Chen (The AAPS Journal, 2022)

Comprehensive analysis of TCR repertoire of COVID-19 patients in different infected stage - Guangyu Wang; Yongsi Wang; Shaofeng Jiang; Wentao Fan; Chune Mo; Weiwei Gong; Hui Chen; Dan He; Jinqing Huang; Minglin Ou; Xianliang Hou (Genes & Genomics, 2022)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Cryptocaryon irritans (Brown, 1951) is a serious threat to aquaculture of marine fish - Yanwei Li; Biao Jiang; Zequan Mo; Anxing Li; Xueming Dan (Reviews in Aquaculture, 2022)
Cryptocaryon irritans (Brown, 1951) is an obligate parasite that mainly invades the skin, fins and gills of marine fish and causes marine ‘white spot disease’. It is common to aquarium and maricultured fish and causes high mortality due to its widespread geographical distribution, indiscriminate host specificity, short and simple life cycle, and high level of virulence. Numerous physical methods and chemical bath agents are applied to cure this disease in closed, re‐circulating aquaculture systems, but these treatments are not suitable in open environments such as cages and ponds. Fortunately, new measures, such as oral chemical drugs, oral plant components, vaccines and even biological control, are being developed as promising methods to treat and prevent cryptocaryoniasis in open aquaculture systems. Here, we provide a broad overview of C . irritans research, focussing primarily on work conducted in the last decade that may offer new insights into the treatment of disease in a practical setting.

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Biochar derived from chicken manure as a green adsorbent for naphthalene removal - Chenchen Liu; Zhihong Yin; Dan Hu; Fan Mo; Ruoyu Chu; Liandong Zhu; Chaozhen Hu (Environmental Science and Pollution Research, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Evaluation of subsurface, mulched and non-mulched surface drip irrigation for maize production and economic benefits in northeast China - Dan Wang; Guangyong Li; Yan Mo; Ding Zhang; Xinhan Xu; Carol Jo Wilkerson; Gerrit Hoogenboom (Irrigation Science, 2021)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Controlled-source electromagnetic data processing based on gray system theory and robust estimation - Dan Mo; Qi-Yun Jiang; Di-Quan Li; Chao-Jian Chen; Bi-Ming Zhang; Jia-Wen Liu (Applied Geophysics, 2017)

Comparative transcriptomes and reciprocal best hit analysis revealed potential pigment genes in two color forms of Tetranychus urticae - Yi-Dan Mo; Si-Xia Yang; Jing-Yu Zhao; Peng-Yu Jin; Xiao-Yue Hong (Experimental and Applied Acarology, 2017)

Outbreak of Edwardsiella tarda infection in farm-cultured giant mottled eel Anguilla marmorata in China - Ze-Quan Mo; Ling Zhou; Xiang Zhang; Lian Gan; Li Liu; Xue-Ming Dan (Fisheries Science, 2015)

Alternating Magnetic Field-Induced Hyperthermia Increases Iron Oxide Nanoparticle Cell Association/Uptake and Flux in Blood–Brain Barrier Models - Mo Dan; Younsoo Bae; Thomas A. Pittman; Robert A. Yokel (Pharmaceutical Research, 2015)

Orange‐spotted grouper Epinephelus coioides Tak1: molecular identification, expression analysis and functional study - Y. W. Li; X. Li; Z. Wang; Z. Q. Mo; X. M. Dan; X. C. Luo; A. X. Li (Journal of Fish Biology, 2015)
In this study, the complementary (c)DNA sequence encoding orange‐spotted grouper Epinephelus coioides Tak1 ( ectak1 ) was cloned, which has an open reading frame of 1728 bp that encodes 575 amino acids (aa). Sequence analysis indicated that Ectak1 contains two characteristic conserved domains, i.e . an N‐terminal serine–threonine protein kinase catalytic domain (27–275 aa) and a C‐terminal coiled‐coil region (499–562 aa). Ectak1 shares high sequence identity with Tak1 from other fish species, especially those of Nile tilapia Oreochromis niloticus (96%) and zebra mbuna Maylandia zebra (96%). ectak1 transcripts were expressed broadly in all of the tissues tested, but ectak1 expression was reduced mainly in the local infection sites (skin and gill) after infection with Cryptocaryon irritans . Intracellular localization analysis showed that Ectak1 was distributed mainly in the cytoplasm. A luciferase reporter assay showed that Ectak1 significantly impaired the NF ‐κ B activity induced by E. coioides Myd88 and Traf6. Overall, these results suggest that Ectak1 functions to reduce the activity of NF ‐κ B induced by toll‐like receptor ( TLR ) signal molecules in HEK‐293T cells, and it might have an important role in host defences against parasitic infections.

Block Copolymer Cross-Linked Nanoassemblies Improve Particle Stability and Biocompatibility of Superparamagnetic Iron Oxide Nanoparticles - Mo Dan; Daniel F. Scott; Peter A. Hardy; Robert J. Wydra; J. Zach Hilt; Robert A. Yokel; Younsoo Bae (Pharmaceutical Research, 2013)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Hydrogen sulfide protects H9c2 cells against doxorubicin-induced cardiotoxicity through inhibition of endoplasmic reticulum stress - Xiu-Yu Wang; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Ai-Ping Lan; Zhan-Li Yang; Fen Hu; Pei-Xi Chen; Xin-Xue Liao; Jian-Qiang Feng (Molecular and Cellular Biochemistry, 2012)

Inhibition of ROS-activated ERK1/2 pathway contributes to the protection of H2S against chemical hypoxia-induced injury in H9c2 cells - Xiao-Bian Dong; Chun-Tao Yang; Dong-Dan Zheng; Li-Qiu Mo; Xiu-Yu Wang; Ai-Ping Lan; Fen Hu; Pei-Xi Chen; Jian-Qiang Feng; Mei-Fen Zhang; Xin-Xue Liao (Molecular and Cellular Biochemistry, 2012)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)